2013
DOI: 10.1007/s00592-013-0522-6
|View full text |Cite
|
Sign up to set email alerts
|

A CHO/fibre diet reduces and a MUFA diet increases postprandial lipaemia in type 2 diabetes: no supplementary effects of low-volume physical training

Abstract: The aim of the study was to evaluate the effects of a supervised physical training added to a healthy diet-rich in either carbohydrate and fibre (CHO/fibre) or monounsaturated fatty acids (MUFA)-on postprandial dyslipidaemia, an independent cardiovascular risk factor particularly relevant in type 2 diabetes (T2D). Participants were forty-five overweight/obese subjects with T2D, of both genders, in good blood glucose control with diet or diet+metformin, with normal fasting plasma lipids. According to a parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Adherence rate of currently-published RCT of HC diets was 65%–84%, and this was not inferior to the LC diet adherence rate [22,23,26]. Moreover, studies of HC diet with high fiber showed good adherence of participants [36,37]. …”
Section: Literature About the Effects Of High Carbohydrate On Metamentioning
confidence: 98%
See 1 more Smart Citation
“…Adherence rate of currently-published RCT of HC diets was 65%–84%, and this was not inferior to the LC diet adherence rate [22,23,26]. Moreover, studies of HC diet with high fiber showed good adherence of participants [36,37]. …”
Section: Literature About the Effects Of High Carbohydrate On Metamentioning
confidence: 98%
“…An RCT by Bozzetto L et al evaluated the effects of a diet rich in either carbohydrate/fiber with a low GI (moderate carbohydrate/fiber diet; C:F:P = 52%:30% (MUFA 16%):18%, 28 g/1000 kcal for fiber, GI (bread reference) of 48 and mean GL of 15,651) or rich in monounsaturated fatty acids (MUFA diet; C:F:P = 40%:42% (MUFA 28%):18%, 10 g/1000 kcal for fiber, GI (bread reference) of 60 and mean GL of 20,326) on postprandial dyslipidemia in 38 patients with T2DM [37]. After eight weeks, postprandial triglyceride levels decreased after a moderate carbohydrate diet rich in fiber, but increased after MUFA diet ( p < 0.05).…”
Section: Are All Carbohydrates the Same? Does Carbohydrate Type Mamentioning
confidence: 99%
“…[36] The effects of dietary fiber on reducing the body fat stores might be due to reducing the energy intake and chylomicron concentrations and increasing the fat excretion. [37] Moreover, high fiber intake will increase the blunted postprandial, which consequently improves the insulin sensitivity. [38]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared the effects on PPL of a diet high in total fat and MUFA (HFMUFA) (olive oil) vs. low in fat and high in carbohydrates (LFHC) and/or vs. a diet high in fat and SFA (HFSFA) (butter). Many (21,24,33,34,39,46,68,69,76,79,90), but not all (4,14,20,26,65,70,71,85), found that the HFMUFA diet was superior to the other two diets in several aspects of postprandial TAG metabolism in both healthy and nonhealthy volunteers (Tables 1 and 2).…”
Section: Amount and Type Of Fatmentioning
confidence: 99%
“…Small sample size, no washout period, only small differences (ϳ3%) between diets in MUFA, higher fiber content in LFHC, or short postprandial time may account for the results of these studies. More importantly, in some of these studies, test meal composition was according to diet composition, and the LFHC meal had less (14,20), or no (65) fat compared with the HFMUFA meal; therefore, this effect was expected, since meal total fat amount is the main determinant of PPL (14,20,65). However, other studies found benefits of a HFMUFA vs. a LFHC diet, even if the test meal was according to diet composition and therefore of greater fat (24,33,68,79).…”
Section: Amount and Type Of Fatmentioning
confidence: 99%